2005
DOI: 10.1210/me.2004-0312
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Glucagon-Like Peptide-1 Receptor β-Arrestin 2 Interaction: A High-Affinity Receptor Phenotype

Abstract: To dissect the interaction between beta-arrestin ((beta)arr) and family B G protein-coupled receptors, we constructed fusion proteins between the glucagon-like peptide 1 receptor and (beta)arr2. The fusion constructs had an increase in apparent affinity selectively for glucagon, suggesting that (beta)arr2 interaction locks the receptor in a high-affinity conformation, which can be explored by some, but not all, ligands. The fusion constructs adopted a signaling phenotype governed by the tethered (beta)arr2 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 43 publications
6
67
1
Order By: Relevance
“…Moreover, the fraction of receptor molecules in the high agonist affinity state in the presence of both G protein and arrestin was found to be directly proportional to the intrinsic activity of the agonist (Samama et al, 1993;Simons et al, 2004). Similar observations with the N-formyl peptide receptor Key et al, 2001Key et al, , 2003 and glucagon-like peptide-1 receptor (Jorgensen et al, 2005) strongly indicate that this is a general rule for the GPCR family. The translocation of arrestin-GFP fusion proteins to the plasma membrane in response to receptor activation is a popular indicator of arrestin binding to the receptor in living cells .…”
Section: Do G Proteins and Arrestins Require The Same "Active" Receptsupporting
confidence: 70%
“…Moreover, the fraction of receptor molecules in the high agonist affinity state in the presence of both G protein and arrestin was found to be directly proportional to the intrinsic activity of the agonist (Samama et al, 1993;Simons et al, 2004). Similar observations with the N-formyl peptide receptor Key et al, 2001Key et al, , 2003 and glucagon-like peptide-1 receptor (Jorgensen et al, 2005) strongly indicate that this is a general rule for the GPCR family. The translocation of arrestin-GFP fusion proteins to the plasma membrane in response to receptor activation is a popular indicator of arrestin binding to the receptor in living cells .…”
Section: Do G Proteins and Arrestins Require The Same "Active" Receptsupporting
confidence: 70%
“…By stabilizing a receptor's active conformation, arrestin increases its affinity for agonist (Gurevich et al, 1997;Key et al, 2001;Martini et al, 2002;Key et al, 2003;Jorgensen et al, 2005). As shown in Table 1, arrestin caused a profound increase in agonist affinity for all of the TRH receptors studied.…”
Section: Discussionmentioning
confidence: 89%
“…Because β-arrestin recruitment is dependent on receptor phosphorylation by GRKs, β2-AR/Rluc was cotransfected with GRK 2 or GRK 5 for potential optimization of receptor phosphorylation. Jorgensen et al 20 have shown that this enhances the sensitivity of the BRET 2 assay. Moreover, McGraw and Liggett 21 demonstrated that a relatively low level of GRK 2 expression in human airway smooth muscle (HASM) is associated with an attenuated rate of short-term agonist-promoted β2-AR desensitization.…”
Section: Resultsmentioning
confidence: 98%